2001
DOI: 10.1038/sj.bmt.1702785
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of idiotypic protein primed allogeneic marrow grafts elicits potent graft-versus-myeloma effects in mice

Abstract: Summary:The active immunization of bone marrow (BM) donors with myeloma immunoglobulin (Ig) results in an idiotypic T cell response that can be transferred to the recipient. Using a murine model we evaluated the effectiveness, side-effects and underlying mechanisms of this approach. Balb/c (H-2 d ) mice were given a dose of HOPC-1F myeloma cells secreting the monoclonal IgG 2a followed by lethal total body irradiation (7.5 Gy) 2 days later and a subsequent transplantation of 2 ؋ 10 7 allogeneic MHC-matched DBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Utilising the same myeloma model we recently showed that immunisation of healthy MHC-identical bone marrow donors with the HOPC-derived idiotype protein induced a powerful antitumoural effect post transplant in which Idspecific CD8 + T cells were involved. 32 These data are in line with recent studies in humans by Li et al 33 demonstrating that idiotype-specific CD8 + T cells derived from immunised healthy stem cell donors can recognise and kill fresh autologous myeloma cells. In the autologous setting, Ö sterborg and coworkers 34 treated myeloma patients with the purified serum M-component by repeated intradermal injections together with soluble granulocyte-macrophage colony-stimulating factor (GM-CSF).…”
Section: Discussionsupporting
confidence: 81%
“…Utilising the same myeloma model we recently showed that immunisation of healthy MHC-identical bone marrow donors with the HOPC-derived idiotype protein induced a powerful antitumoural effect post transplant in which Idspecific CD8 + T cells were involved. 32 These data are in line with recent studies in humans by Li et al 33 demonstrating that idiotype-specific CD8 + T cells derived from immunised healthy stem cell donors can recognise and kill fresh autologous myeloma cells. In the autologous setting, Ö sterborg and coworkers 34 treated myeloma patients with the purified serum M-component by repeated intradermal injections together with soluble granulocyte-macrophage colony-stimulating factor (GM-CSF).…”
Section: Discussionsupporting
confidence: 81%
“…35 Idiotype protein vaccination of donor DBA/2 (H-2 d ) mice, similarly, induced GvT against the HOPC myeloma after BMT using BALB/c (H-2 d ) recipients, but it is not clear whether GvT was mediated by T cells and/or antibody in this model. 37 In the current study, the GvT reactions that resulted in cures required the adoptive transfer of donor CD4 ϩ T cells combined with CD8 ϩ T cells. Transplantation of the CD4 ϩ or CD8 ϩ T cells from WT1-vaccinated donors failed to protect against FBL3 leukemia progression.…”
Section: Donor Immunization Augments Gvt 5327mentioning
confidence: 99%
“…Currently, only two immunocompetent murine models have been described in which allo-SCT is associated with a GvM effect [13], [14], but these models do not resemble human MM disease [13] or do not use allo-SCT as a curative treatment for established disease [14]. So far, an immunocompetent murine GvM model in which allo-SCT is used for the treatment of established MM that resembles human disease, marked by bone marrow tropism and osteolytic lesions, has not been described.…”
Section: Introductionmentioning
confidence: 99%